The Cornella Health Interview Survey Follow-Up (CHIS.FU) Study: design, methods, and response rate - Perez Gloria; Salto Esteve; Marti Merce; Fernandez Esteve; Schiaffino Anna; Garcia Montse; Peris Merce; Borrell Carme; Nieto F Javier; Borras Josep Maria (BMC, 2003)
Abstract Background The aim of this report is to describe the main characteristics of the design, including response rates, of the Cornella Health Interview Survey Follow-up Study. Methods The original cohort consisted of 2,500 subjects (1,263 women and 1,237 men) interviewed as part of the 1994 Cornella Health Interview Study. A record linkage to update the address and vital status of the cohort members was carried out using, first a deterministic method, and secondly a probabilistic one, based on each subject's first name and surnames. Subsequently, we attempted to locate the cohort members to conduct the phone follow-up interviews. A pilot study was carried out to test the overall feasibility and to modify some procedures before the field work began. Results After record linkage, 2,468 (98.7%) subjects were successfully traced. Of these, 91 (3.6%) were deceased, 259 (10.3%) had moved to other towns, and 50 (2.0%) had neither renewed their last municipal census documents nor declared having moved. After using different strategies to track and to retain cohort members, we traced 92% of the CHIS participants. From them, 1,605 subjects answered the follow-up questionnaire. Conclusion The computerized record linkage maximized the success of the follow-up that was carried out 7 years after the baseline interview. The pilot study was useful to increase the efficiency in tracing and interviewing the respondents.